PERANCANGAN START UP DIGITAL ENT BABY EQUIPMENT AND TOYS RENTAL DENGAN METODE USER DESIGN CENTER - M A, M Lutfi; Febriani, Yeza; Kapti, Kapti (LP2M Institut Informatika Dan Bisnis Darmajaya, 2024)
The digital start-up ENT Baby Equipment and Toys Rental was founded with the aim of meeting families' needs for baby equipment and various toys that can be rented for a certain period of time. Because the use of equipment, equipment and toys for babies and children is relatively short and not everyone can afford it, this rental service is very helpful for those who have limited funds. ENT can be accessed via the ENT Mobile Apps application online with the aim of making it easier for consumers to choose the items they want to rent without having to come directly to the equipment rental place. ENT is affiliated with several trusted and registered baby equipment and toy rental partners. In this way, ENT will bridge between consumers and rental partners for baby equipment and children's toys. The design method uses the User Center Design method, while the business process analysis uses the SWOT method and needs analysis uses the TELOS analysis method. Based on Usability Testing using the Usability Heuristic method approach, the average indicator assessment was 86%. This shows that the ENT digital start-up application gives an intuitive and user-friendly impression so that it can be accepted and easy to understand by users.